Expression of nonclassical molecule human leukocyte antigen-G in oral lesions - Fregonezi, Paula A. G. [UNESP]; Silva, Tarsia G. A. [UNESP]; Simoes, Renata T.; Moreau, Philipe; Carosella, Edgardo D.; Klaey, Carla P. M.; Goncalves, Maria A. G.; Soares, Edson G.; Souto, Francisco; Donadi, Eduardo A.; Soares, Christiane P. [UNESP] (W B Saunders Co-elsevier Inc, 2012)
Introduction: Human leukocyte antigen (HLA)-G is a nonclassic class I molecule that acts as a modulator of immune responses, and the expression of these molecules in virus-infected cells has been associated with subversion of the immune response.Objective: In this study, we performed a cross-sectional study, systematically comparing the expression of the HLA-G in benign, premalignant, and malignant oral lesions and correlating it with the presence of high-risk and low-risk human papillomavirus (HPV) types.Specimens and Methods: Oral biopsies were collected from 51 patients and analyzed by immunohistochemistry using anti HLA-G antibody. Human papillomavirus detection and typing from oral biopsies were obtained by polymerase chain reaction using GP5+/GP6+ and specific primers.Results: The 51 biopsies were stratified into 3 groups according to lesion grade: oral benign lesions (oral hyperplasia and papilloma, n = 16), oral premalignant lesions (oral leukoplakia with dysplasia and lichen planus, n = 17), and malignant lesions (oral squamous cell carcinoma, n = 18). Human leukocyte antigen G overexpression was mainly observed in benign and premalignant oral lesions but was not related to HPV infection (P>.05). on the other hand, HPV DNA was detected in 24 (47%) oral lesions, mainly in benign and premalignant lesions, with the most frequent type detected being high-risk HPV type.Conclusion: The HLA-G molecule was expressed in a significant number of benign oral lesions and was not correlated with HPV infection or oral cancer. Crown Copyright (C) 2012 Published by Elsevier B.V. All rights reserved.